1997
DOI: 10.1080/00288330.1997.9516744
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing autotrophic and heterotrophic nanoflagellate abundance in five water masses surrounding New Zealand

Abstract: The aim of this study was to measure nanoflagellate abundance in New Zealand waters, and identify the key factors which both influence, and are influenced by, nanoflagellate abundance. Nanoflagellate populations were sampled in winter and spring 1993 from a series of sites representing different water masses around the South Island of New Zealand. Both numbers and biomass of heterotrophic (HNF) and autotrophic nanoflagellate (ANF) populations were larger in spring by a factor of four. ANF were about three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
5
19
6
Order By: Relevance
“…This suggests that the bacterial populations in this study were potentially 'top-down' controlled by grazing pressure (Ducklow 1992). These results are consistent with those of Smith & Hall (1997) and Safi & Hall (1997), who suggested that in both seasons during this study the heterotrophic nanoflagellates were potentially food-limited, indicating that top-down grazing pressures may be limiting bacterial populations in the region. In this study the bacterial biomass was almost as great or greater than phytoplankton biomass in SA waters in both seasons and in the ST waters in spring, suggesting that the microbial food web was playing a significant role in the overall food web structure in these water masses and seasons.…”
Section: Heterotrophic Bacteriasupporting
confidence: 82%
See 1 more Smart Citation
“…This suggests that the bacterial populations in this study were potentially 'top-down' controlled by grazing pressure (Ducklow 1992). These results are consistent with those of Smith & Hall (1997) and Safi & Hall (1997), who suggested that in both seasons during this study the heterotrophic nanoflagellates were potentially food-limited, indicating that top-down grazing pressures may be limiting bacterial populations in the region. In this study the bacterial biomass was almost as great or greater than phytoplankton biomass in SA waters in both seasons and in the ST waters in spring, suggesting that the microbial food web was playing a significant role in the overall food web structure in these water masses and seasons.…”
Section: Heterotrophic Bacteriasupporting
confidence: 82%
“…The proportion of the biomass contributed by heterotrophic nanoflagellates increased between winter and spring in all water types. The lower proportion of heterotrophic nanoflagellates in winter may be due to increased grazing pressure by ciliates, which may have also resulted in the decrease in size of the heterotrophic nanoflagellates observed (Safi & Hall 1997). These results are consistent with Boyd et al (1995a), who also showed that the ciliate population was a larger proportion of the microzooplankton population in winter in the subarctic North Pacific.…”
Section: Microzooplanktonsupporting
confidence: 81%
“…Bacterial numbers across all 3 water masses were higher than previously reported in this region (Safi & Hall 1997, Smith & Hall 1997) and ranged from 1.6 X 106 to 2.9 X 106 a able 1). These observations are similar to Cho & Azam (1990), who report that in low chl a environments, bacterial carbon can often exceed phytoplankton carbon, commonly contributing 2 to 3 times the carbon of phytoplankton.…”
Section: Role Of the Microbial Food Web In The Convergence Zonecontrasting
confidence: 43%
“…In this water mass we regarded 90% of the phototrophic nanoflagellates as MNF and adjusted all grazing calculations accordingly. HNF biovolume was approximately twice MNF biovolume in all water masses, which was opposite to the general trend reported previously in this region for winter and spring seasons (James & Hall 1996, Safi & Hall 1997. HNF biovolumes were similar between convergence and subtropical waters, with a mean biovolume at 10 m of 37.7 and 37.4 pm3, respectively.…”
Section: Planktonic Abundancecontrasting
confidence: 42%
“…HNF and PNF were prepared for microscopy by filtering 20 to 50 ml DAPI-stained water through a 0.6 µm 25 mm black polycarbonate membrane as in Safi & Hall (1997). Slides were frozen until examination under UV excitation at 1000× magnification using a Leica Leitz DMRB epifluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%